2010
DOI: 10.1049/iet-cta.2008.0613
|View full text |Cite
|
Sign up to set email alerts
|

Optimal usage of coal, gas and oil in a power plant

Abstract: This study addresses the problem of an optimal actuator selection when economic value is considered. The objective is to minimise the economical cost of operating a given plant. The problem has been formulated using mathematic notions from economics. Functionals describing the business objectives of operating a power plant has been established. The selection of actuator configuration has been limited to the fuel system which in the considered plant consists of three different fuels -coal, gas and oil. The chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Therefore, some heuristics are introduced to avoid the reference deviations (and non-optimal behavior). From the discrete optimization, it is observed that only one fuel is used at the time, which has also been suggested by earlier work [10], [13]. As a consequence, σ i,j (t) < 0 at any given time, where the notation x i,j means coordinates i and j of the vector x.…”
Section: Optimal Feedbacksupporting
confidence: 53%
See 4 more Smart Citations
“…Therefore, some heuristics are introduced to avoid the reference deviations (and non-optimal behavior). From the discrete optimization, it is observed that only one fuel is used at the time, which has also been suggested by earlier work [10], [13]. As a consequence, σ i,j (t) < 0 at any given time, where the notation x i,j means coordinates i and j of the vector x.…”
Section: Optimal Feedbacksupporting
confidence: 53%
“…The functions in (4) are in this work assumed sufficiently smooth (C and explanation of the above quantities can be found in [14], [12], [13], and [10]. A prognosis of the next days's electricity consumption is established by Energinet.dk 4 , which is responsible for the electrical grid in Denmark.…”
Section: Problem Formulationmentioning
confidence: 99%
See 3 more Smart Citations